PENGARUH NILAI PERUSAHAAN PADA PERUSAHAAN PARIWISATA & PERHOTELAN DI BURSA EFEK INDONESIA PERIODE 2020 – 2022 - Ngesthi, Priscilla Oliviane; Setijaningsih, Herlin Tundjung (Fakultas Ekonomi Universitas Tarumanagara, 2025)
This research examines that during the Covid-19 pandemic, tourism & hospitality companies on the IDX experienced a continuous decline in company value from 2020 - 2022 even though the company had already made large profits in 2022. This decline in company value was also followed by a decline in the proportion of institutional ownership as a whole. continuously and the proportion of managerial ownership is unstable from 2020 – 2022, (based on financial report data on the IDX). This was also influenced by companies that did not implement Corporate Social Responsibility (CSR) during the Covid-19 pandemic by being unable to pay dividends to shareholders, laying off employees and carrying out mass layoffs. The lack of implementation of CSR will cause a decrease in the proportion of institutional ownership and managerial ownership, and will affect the value of the company. This research uses quantitative methods and takes data from financial reports registered on the IDX for the period 2020 - 2022. The results of the research show that institutional ownership and managerial ownership have a negative effect on company value, CSR can moderate and strengthen the influence of institutional ownership on company value, but CSR has not able to moderate the influence of managerial ownership on company value.